Towards a Metadata Schema for Characterizing Lesson Plans supported by Virtual and Remote Labs in School Education - Zervas, P.; Tsourlidaki, E.; Sotiriou, S.; Sampson, Demetrios (2015)
Technological advancements in the field of World Wide Web have led to a plethora of remote and virtual labs (RVLs) that are currently available online and they are offered with or without cost. However, using a RVL to teach a specific science subject might not be a straightforward task for a science teacher. As a result, science teachers need to be able to find existing lesson plans supported by RVLs (designed by other science teachers), so as to (a) be informed on how specific RVLs can be used in the context of a science education lesson and (b) be inspired and possibly adapt existing lesson plans supported by RVLs to cover their specific teaching needs. The most common way to facilitate this process using web technologies is to (a) characterize lesson plans with appropriately selected educational metadata and (b) to build a web repository that collects the metadata descriptions of lesson plans following a common metadata schema and offers search and retrieval facilities. Within this context, the scope of this paper is twofold: (a) to propose a metadata schema that can be used for characterizing school science education lesson plans supported by RVLs and (b) to validate this metadata schema with 82 European school science teachers that was performed in the framework of a major European Initiative namely, the Go-Lab project, so as to identify which metadata elements are considered important when science teachers are searching in web-based repositories.